Anxiety, self-compassion, perceived social support and resilience in two groups of primiparous pregnant women fully and not attending childbirth preparation classes - Hadiseh Hajihatamloo; Marzieh Ebrahimi; Vahid Alinejad; Roghieh Bayrami (BMC Psychology)
Abstract Background Pregnancy involves a combination of physical, social, and emotional changes that can lead to mental health issues, potentially impacting fetal health, childbirth success, and breastfeeding. The present study was conducted to compare anxiety, self-compassion, perceived social support and resilience in two groups of primiparous pregnant women who were either not attending or, fully attending childbirth preparation classes. Methods This descriptive-analytic cross-sectional study included 210 pregnant women who attended comprehensive health centers in Khoy from 2023 to 2024. Participants were selected through random sampling. Data were collected using a demographic characteristics form, the Self-Compassion Scale - Short Form (SCS-SF), the Connor-Davidson Resilience Scale (CD-RISC), the Pregnancy-Related Anxiety Questionnaire - Revised 2 (PRAQ-R2), and the Multidimensional Scale of Perceived Social Support (MSPSS). The specific statistical tests (chi-square, independent t-test, Mann-Whitney U) were used in SPSS 16 software, at a significance level of p < 0.05. Results The mean score of anxiety was lower in the group of pregnant women fully attending the classes compared to the non-attending group of women (p < 0.001). Additionally, mean scores of self-compassion(p < 0.001), resilience(p < 0.001), and perceived social support (p < 0.001) were significantly higher among women fully attending these classes (p < 0.001). Conclusion Given the lower anxiety and higher self-compassion, resilience, and perceived social support observed in women fully attending childbirth preparation classes, healthcare providers should consider implementing supportive interventions to enhance maternal mental health.